Communication strategy of Bumdes Sarwada Amertha in the management of Taro tourism village towards independent tourism village - Ida Bagus Ketut Surya; Ida Ayu Anggreni Suryaningsih (Politeknik Negeri Bali, 2023)
This study discusses the communication strategy carried out by BUMDes Sarwada Amertha in managing Taro Tourism Village towards an independent tourism village. The communication strategy used is to use the POAC management communication strategy method, the purpose of this study is to find out how the communication strategy knows the audience, determines goals, compiles messages and establishes methods and media. Data obtained through observation and in-depth interviews. The authors took three informants to supplement the research data. The conclusion of this study are (1) Planning, BUMDes Sarwada Amertha plans to maximize the visits of tourists who come to Taro Tourism Village every month and intensify promotions both conventionally and through online media. (2) Organizing, in managing existing business units, BUMDes Sarwada Amerhta has a management organizational structure. (3) Actuating, BUMDes manager Sarwada Amertha implements the work plan well in order to achieve the existing vision and mission. (4) Controlling, BUMDes Sarwada Amertha as a legal umbrella that accommodates all tourist attractions in Taro Tourism Village. it can be concluded that the communication strategy carried out by BUMDes Sarwada Amertha in the management of Taro Tourism Village as an independent tourism village by carrying out a communication strategy using POAC management principles.